1998
DOI: 10.1074/jbc.273.40.25893
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Characteristics, Subcellular Localization, and Substrate Specificity of DYRK-related Kinases, a Novel Family of Dual Specificity Protein Kinases

Abstract: DYRK1 is a dual specificity protein kinase presumably involved in brain development. Here we show that the kinase belongs to a new family of protein kinases comprising at least seven mammalian isoforms (DYRK1A, DYRK1B, DYRK1C, DYRK2, DYRK3, DYRK4A, and DYRK4B), the yeast homolog Yak1p, and the Drosophila kinase minibrain (MNB). In rat tissues, DYRK1A is expressed ubiquitously, whereas transcripts for DYRK1B, DYRK2, DYRK3, and DYRK4 were detected predominantly in testes of adult but not prepuberal rats. By fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
281
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(299 citation statements)
references
References 41 publications
14
281
1
3
Order By: Relevance
“…We have previously found that an expression construct of the yeast kinase Yak1p consisting only of the catalytic domain and the adjacent DYRK homology box is capable of tyrosine autophosphorylation in E. coli [46]. Here we show that analogous constructs of DYRK2, HIPK2 and CLK1 also autophosphorylate in E. coli.…”
Section: Tyrosine Autophosphorylation Of Other Cmgc Kinasesmentioning
confidence: 73%
See 1 more Smart Citation
“…We have previously found that an expression construct of the yeast kinase Yak1p consisting only of the catalytic domain and the adjacent DYRK homology box is capable of tyrosine autophosphorylation in E. coli [46]. Here we show that analogous constructs of DYRK2, HIPK2 and CLK1 also autophosphorylate in E. coli.…”
Section: Tyrosine Autophosphorylation Of Other Cmgc Kinasesmentioning
confidence: 73%
“…Mammalian expression plasmids for the DYRKs and CLK3 have been described previously [35,46]. A deletion construct (GFP-DYRK1A-DNDC) was generated that contained only the catalytic domain and the DYRK homology box (amino acids 135-481; numbering in this paper refers to the splicing variants defined as 'canonical' in the UniProt database www.uniprot.org).…”
Section: Plasmidsmentioning
confidence: 99%
“…We were interested in whether Hap1 and DYRK1A interact with Dcaf7 competitively or synergistically. First, however, we wanted to examine the subcellular localization of DYRK1A, because studies have demonstrated both cytoplasmic and nuclear distribution of endogenous DYRK1A in neuronal cells, whereas ectopically expressed DYRK1A is found mainly in the nucleus (37)(38)(39)(40)(41). We found via subcellular fractionation and immunostaining that endogenous DYRK1A is localized predominantly in the cytoplasm in mouse brain in vivo and in cultured HEK293 and PC12 cells (Fig.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 99%
“…1 Mirk is a member of a multigene family, called the minibrain/dyrk family. [2][3][4][5] Mutant minibrain flies are characterized by a marked reduction in size of the optic lobes and central brain hemispheres, 2 suggesting that minibrain plays a role in neuronal survival and/or proliferation. In cell culture systems, dyrk1A mediates neuronal differentiation by phosphorylating CREB in vivo, leading to the stimulation of subsequent CRE-mediated transcription during neuronal differentiation in hippocampal progenitor cells.…”
mentioning
confidence: 99%
“…All dyrk family members are serine/threonine kinases that also can autophosphorylate on tyrosine, so they are dual-function kinases. [2][3][4][5] Their activation sequence is YQY or YTY, with both tyrosines phosphorylated. This YxY sequence aligns with the TxY activation sequence in MAPKs.…”
mentioning
confidence: 99%